Robust mode-locking in a hybrid ultrafast laser based on nonlinear multimodal interference. (April 2023) - Liu, Xuanyi; Dai, Maolin; Pan, Denghui; Lin, Kaibin; Malomed, Boris A.; Li, Qian; Fu, H.Y.
Highlights: The first half-polarization-maintaining (half-PM) fiber laser mode-locked with a reflective multimode interference saturable absorber (SA) has been demonstrated. The proposed fiber laser employs a PMF-GIMF-SMF structure as a mode-locking SA, which has never been implemented in previously reported GIMF-based fiber lasers. The use of PM fibers can enhance their environmental stability. The output power fluctuation over 24 h, short- and long-spectral stability, and noise performance have been characterized to verify the practicability of our fiber laser. Abstract: We experimentally demonstrate the realization of a half-polarization-maintaining (half-PM) fiber laser, in which mode-locking is provided by a reflective multimode-interference saturable absorber (SA). In the specially designed SA, linearly polarized light is coupled into a 15-cm-long graded-index multimode fiber (GIMF) through the PM fiber, and then reflected back to the PM structure through a mirror pigtailed with a single-mode fiber (SMF). The modulation depth and saturation peak power are measured to be 1.5 % and 0.6 W, respectively. The proposed SA device is incorporated into a novel half-PM erbium-doped fiber oscillator, which generates soliton pulses with 409 fs temporal duration at a 33.3 MHz repetition rate. The proposed fiber laser is compared to a conventional non-PM fiber laser mode-locked by the nonlinear polarization evolution (NPE) in terms of essential optical properties such as the spectral bandwidth, pulse duration, and stability performance. Short- and long-time stability tests and superior noise performance corroborate robust mode-locking in this setup.